2023
DOI: 10.3390/pharmaceutics15041067
|View full text |Cite
|
Sign up to set email alerts
|

Newly Synthesized Lignin Microparticles as Bioinspired Oral Drug-Delivery Vehicles: Flavonoid-Carrier Potential and In Vitro Radical-Scavenging Activity

Abstract: The aim of the present study was to synthesize lignin microparticles, to evaluate their physicochemical, spectral, morphological and structural characteristics, to examine their encapsulation and in vitro release potential and behaviour towards the flavonoid morin in simulated physiological medium and to assess the in vitro radical-scavenging potential of the morin-loaded lignin microcarrier systems. The physicochemical, structural and morphological characteristics of alkali lignin, lignin particles (LP) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Moreover, the higher DPPH radical scavenging activity of vitamin K 3 as compared to that of naringenin indicated that an increase in the number of phenolic hydroxyl groups did not necessarily lead to higher antioxidant potential values. Similar results were observed by Ivanova et al (2023) [32].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, the higher DPPH radical scavenging activity of vitamin K 3 as compared to that of naringenin indicated that an increase in the number of phenolic hydroxyl groups did not necessarily lead to higher antioxidant potential values. Similar results were observed by Ivanova et al (2023) [32].…”
Section: Resultssupporting
confidence: 89%
“…The absorbance was measured at λ = 517 nm. DPPH-scavenging activity (DPPH, %) was calculated according to [32].…”
Section: Radical Scavenging Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also information about the antioxidant, antiviral, antimicrobial, anticoagulant, and immune modulator capabilities of lignin and its derivatives [ 26 , 27 , 28 , 29 ]. Due to their biodegradability and biocompatibility, lignins possess characteristic marks to be involved in nanomedicine as precursors for the development of drug-delivery system(s) [ 30 , 31 ], but additional studies on their effect on intracellular homeostasis have to be performed.…”
Section: Introductionmentioning
confidence: 99%